Assessing Soil Salinity Risk in the RUT Irrigation District, Colombia (Orinoquia, 2017)
The water resources mismanagement is a common concern in the agriculture, and this issue is boosting salinity processes in the Colombian lands. Thus, this paper aimed to assess the soil salinity risk in the RUT irrigation district for sugarcane, grape, and passion fruit by coupling SOSALRIEGO-GIS. First, sources of surface water and their influence areas were identified in the RUT irrigation district. Afterwards, inputs (water ionic constituents, electrical conductivity of rainwater, annual rainfall, crop salt tolerance, soil texture, and leaching fraction) fed in the SOSALRIEGO model, and then, the leaching requirement (LR) of each zone was computed (output) for each crop. Finally, employing GIS, LR values were arranged in categories in order to map the soil salinity risk in the RUT irrigation district for each crop and zone. The soil salinity risk fell into a medium rank for sugarcane, medium to high ranks for grape, and high to very high ranks for passion fruit. Furthermore, the soil salinity risk was higher in zones with poor irrigation water quality. Zones II and III, which canals convey domestic wastewater and drained water fell in greater salinity risk category than zone I, which bears water withdrawal from the Cauca River.
Keywords: irrigation water quality; soil salinization; SOSALRIEGO; risk management